Determinasi Nilai Perusahaan berdasarkan Aspek Total Asset Turn Over, Kepemilikan Manajerial, Keputusan Inverstasi dan Keputusan Pendanaan (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman Periode 2016-2021) - Milawati; Nugroho, Lucky; Bowo Prayoga Kasmo, Arief (Forum Kerjasama Pendidikan Tinggi, 2023)
One of the industries that investors are interested in is the food and beverage industry. However, due to the Covid-19 pandemic in Indonesia, share prices in this industry have decreased significantly and have resulted in a decrease in company value. This study aims to determine the effect of activity ratios, ownership structure, investment decisions and funding decisions on firm value. The populations in this study are food and beverage sub-sector manufacturing companies listed on the IDX for the 2016-2021 period. The design of this research is quantitative research. The research sample consisted of 11 companies selected by purposive sampling. The data used is secondary data with multiple linear regression analysis methods which include descriptive statistical tests, classical assumption tests, model suitability tests, and hypothesis testing. Based on the results of the study indicate that the activity ratio, ownership structure and investment decisions have a significant positive influence on firm value. Meanwhile, funding decisions have no significant effect on firm value.